PENGUJIAN EFEKTIVITAS BEBERAPA ISOLAT CENDAWAN MIKORIZA ARBUSKULA (CMA) TERHADAP BIBIT PISANG (Musa AAB RAJA NANGKA) ASAL KULTUR JARINGAN - Rainiyati; Chozin; Sudarsono; Mansur (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
An experiment to investigate the affectivity five isolat of Arbuscular Mycorrhizal Fungi (AMF) on the growth of banana (Musa sp.) obtained from tissue culture had been conducted at the Plant Biotechnology laboratory, Glasshouse, and Experimental farm of the Faculty of Agriculture Jambi University. The results showed that there were five mycorrhizal isolates that can be tested for their affectivity on banana seedlings. The growth responses of the seedlings inoculated with AMF was higher than those non-inoculated seedlings due to higher rate of nutrient uptake. Each kind of AMF possesses different level of effectiveness on banana seedling. The application of single isolate Glomus sp-1 at acclimatization time resulted that highest effectiveness.